Juridical Analysis of Drug Use and Its Implications in Criminal Law - Muhammad Ridwan Lubis (Jurnal Smart Hukum (JSH), 2024)
The purpose of this study is to evaluate the effectiveness of legal analysis in addressing drug abuse in law enforcement within Indonesia. Identifying the barriers to law enforcement and rehabilitation for drug offenders and narcotics abusers in the legal system is also a focus. The research employs sociological and juridical research methods, incorporating a social science approach alongside legal analysis. To identify issues in this study, the researcher employed descriptive analysis research methods by detailing the application of punishment and rehabilitation approaches for drug dealers and individuals involved in drug abuse.